XVI Powszechny Zjazd Historyków Polskich (Wrocław, 15-18 września 1999) - Jamrożek, Wiesiław (Biuletyn Historii Wychowania, 2000)
XVI Powszechny Zjazd Historyków Polskich (Wrocław, 15-18 września 1999)